Ethos, Ethics, and Spirituality in Minangkabau Petatah-Petitih: A Linguistic-Cultural Alternative to Weber’s Protestant Ethic - Hasanuddin Hasanuddin; Imelda Indah Lestari (Masyarakat Linguistik Indonesia Universitas Andalas, 2026)
The entrepreneurial culture of the Minangkabau is widely regarded as compelling, continually explored and discussed by scholars. It has long been widely recognized that this value system is embedded in a linguistic vessel known as petatah-petitih (traditional Minangkabau proverbs). These proverbs are often regarded as repositories of social norms, yet their role as a living linguistic system actively shaping everyday practices, particularly in the economic sphere, remains largely underexplored. Previous studies have tended to view petatah-petitih as static containers of moral prescriptions. However, their existence as dynamic catalysts of a community’s lived values and guiding principles has remained largely untouched. In fact, petatah-petitih function as a living linguistic system, continuously activated through hermeneutic engagement and practical actualization by social actors within the flow of their daily lives. This article addresses that gap by investigating how petatah-petitih both live and are lived by Minangkabau traders as they negotiate meaning within their entrepreneurial journeys. Drawing on Hymes’ ethnolinguistics and philosophical-phenomenological hermeneutics, the researcher conducted focus group discussions, participatory observation, and hermeneutic interviews with 14 informants across West Sumatra, Bogor, and Bali. Findings reveal that proverbs concerning Minangkabau entrepreneurial culture form an integrative whole, not operating as fixed prescriptions, but as a dynamic ethical framework continually reinterpreted through lived experience. Hermeneutic analysis shows that meaning is constructed dialogically, through a circular movement among text, context, and the interpreter’s subjectivity. This study contributes to decolonial approaches in ethnolinguistics by centering Indigenous interpretive practices as the core of analysis, while also proposing a new methodological model for understanding petatah-petitih as vital resources for building national economic resilience and as a critique of the dominant currents of global capitalism.